What influences the climate entrepreneurship? Chinese-based evidence - Li, Cai; Asim, Shoaib; Khalid, Waleed; Sibt E. Ali, Muhammad (Frontiers in Environmental Science, 2023)
Climate change is the biggest threat to the public as it threatens water scarcity, heat waves, economic losses, and food insecurity. Consequently, the control of climate entrepreneurship is very significant to ensure business sustainability. However, the identification of controlling measures for climate entrepreneurship remained unexplored. Therefore, the purpose of this study was to examine the influence of organizational performance, carbon management practices, and attitudes toward emission trading schemes on climate entrepreneurship. The study is based on 180 respondents from large Chinese firms. Using structural equation modeling, the results report a significantly negative influence of organizational performance, carbon management practices, and attitudes toward emission trading schemes on climate entrepreneurship. This suggests to the management and policymakers that an increase in organizational performance, carbon management practices, and attitude toward emission trading schemes brings a significant decline in climate entrepreneurship and, thus, ensures a sustained business environment. One of the few studies examines variations in company responses to climate change from an entrepreneurial viewpoint. In order to advance the body of knowledge on the strategic management of climate change challenges, the study offers a theoretical foundation. Chinese policymakers are very keen to adopt an emission trading scheme and by the implication of articulate results can help them to attain their climatic goals.